Chronic Elevation of Endothelin-1 Alone May Not Be Sufficient to Impair Endothelium-Dependent Relaxation. Issue 6 (December 2019) - Grunewald, Zachary I.; Jurrissen, Thomas J.; Woodford, Makenzie L.; Ramirez-Perez, Francisco I.; Park, Lauren K.; Pettit-Mee, Ryan; Ghiarone, Thaysa; Brown, Scott M.; Morales-Quinones, Mariana; Ball, James R.; Staveley-O'Carroll, Kevin F.; Aroor, Annayya R.; et al.
Abstract : Endothelin-1 (ET-1) is a powerful vasoconstrictor peptide considered to be causally implicated in hypertension and the development of cardiovascular disease. Increased ET-1 is commonly associated with reduced NO bioavailability and impaired vascular function; however, whether chronic elevation of ET-1 directly impairs endothelium-dependent relaxation (EDR) remains elusive. Herein, we report that (1) prolonged ET-1 exposure (ie, 48 hours) of naive mouse aortas or cultured endothelial cells did not impair EDR or reduce eNOS (endothelial NO synthase) activity, respectively ( P >0.05); (2) mice with endothelial cell–specific ET-1 overexpression did not exhibit impaired EDR or reduced eNOS activity ( P >0.05); (3) chronic (8 weeks) pharmacological blockade of ET-1 receptors in obese/hyperlipidemic mice did not improve aortic EDR or increase eNOS activity ( P >0.05); and (4) vascular and plasma ET-1 did not inversely correlate with EDR in resistance arteries isolated from human subjects with a wide range of ET-1 levels (r=0.0037 and r=−0.1258, respectively). Furthermore, we report that prolonged ET-1 exposure downregulated vascular UCP-1 (uncoupling protein-1; P <0.05), which may contribute to the preservation of EDR in conditions characterized by hyperendothelinemia. Collectively, our findings demonstrate that chronic elevation of ET-1 alone may not be sufficient to impair EDR. Abstract : Supplemental Digital Content is available in the text.